Virtual reality simulation and real-life training programs for cataract surgery: a scoping review of the literature. - Dormegny, Lea.; Lansingh, Van Charles.; Lejay, Anne.; Chakfe, Nabil.; Yaici, Rémi.; Sauer, Arnaud.; Gaucher, David.; Henderson, Bonnie An.; Thomsen, Ann Sofia.; Bourcier, Tristan. (Tufts University. Tisch Library., 2024)
Keywords: Learning, Ophthalmic surgery, Patient safety, Prevention, Simulation, Surgical education, Surgical skills, Training programs, Trainee satisfaction, Virtual reality.; Springer Open.